2021
DOI: 10.1186/s12966-021-01195-8
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluating the reach, effectiveness, adoption, implementation and maintenance of the Resistance Training for Teens program

Abstract: Background Physical activity guidelines recommend young people engage in regular muscle-strengthening activities (e.g., resistance training [RT]). However, few school-based physical activity interventions have been delivered at-scale or promoted RT. The aim of this study was to evaluate the reach, effectiveness, adoption, implementation and maintenance of the Resistance Training for Teens (RT for Teens) program. Methods Data were collected between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 95 publications
0
15
1
Order By: Relevance
“…Of the 115 schools involved in our implementationeffectiveness trial, most were located in major cities, with almost a third from inner regional areas, and the remaining from outer regional areas. Our rate of adoption is lower than has been reported in previous school-based physical activity intervention dissemination studies [43,46]. This may be attributed to a range of factors.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Of the 115 schools involved in our implementationeffectiveness trial, most were located in major cities, with almost a third from inner regional areas, and the remaining from outer regional areas. Our rate of adoption is lower than has been reported in previous school-based physical activity intervention dissemination studies [43,46]. This may be attributed to a range of factors.…”
Section: Discussioncontrasting
confidence: 76%
“…This variability is largely due to the different methods used to calculate reach in dissemination studies [ 9 ]. For example, previous studies have used the number of teachers attending professional learning workshops [ 43 , 44 ] and the ordering of program materials by teachers, to estimate reach into the student population [ 45 ]. We defined ‘reach’ as the estimated number, proportion and representativeness of students who were potentially exposed to iPLAY.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structured sessions of ActTeens Program could offer a feasible method to improve CRF and muscular fitness within PE classes. Further potential advantages are its scalability and ease of dissemination [ 47 , 74 ] since this intervention may be incorporated into PE lessons without taking up additional PE time; it should not interfere with the normal curriculum and does not require extensive training of teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the authors identified errors in the author name and affiliation.…”
mentioning
confidence: 99%